(untitled) (SIRJANĀ – A Journal Of Arts and Art Education, 2023)
This brief piece attempts to describe and identify the terracotta sculptures of three toraṇas at the Śiva temple in Hanuman Dhoka Durbar, which were damaged by the earthquake of 2015. The UNESCO earthquake experts and the JICA archaeological team headed by Moshimichi Okumura recreated the Toranas out of the retrieved artifacts from the debris like a jigsaw puzzle. The significant rubbles were selected and labelled with tags for identification for recreation of the damaged Toranas. In fact, this piece is about the by-product of describing and identifying broken pieces of the terracotta sculptures of Toranas, which the earthquake of 2015 ruined to rubbles.